Palynology - Palynology (Taylor & Francis, 2026)
Palynology was first published in 1977, and is now is a well-established, international journal covering all aspects of the science of organic microfossils and their modern counterparts. We accept papers on both pre-Quaternary and Quaternary palynology, and palaeobotany. Articles across the entire range of palynomorph groups and geological ages are welcomed. Contributions on both the traditional aspects of the subject, and the more novel uses of palynology, are all actively encouraged. We accept suitable manuscripts on, for example, actuopalynology, archaeological palynology, biostratigraphy, floral history, forensic palynology, mellitopalynology and taxonomy. Additionally, book reviews, review articles, papers on methodology and short monographs would all fall within the scope of this journal. The high quality of illustrative material has always been a characteristic of Palynology .
FI 0.59
Q3
Keywords: Biological; Earth & Environmental Food Science; Palinología; Acuerdos transformativos; Transformative agreements; Paleobotánica; Arqueología; Bioestratigrafía